'Everything's been done before': Jean Rhys, Translation, and the Politics of Originality. Issue 4 (November 2019) - Taylor-Batty, Juliette
Abstract : This article explores questions of 'originality' and textual 'ownership' in the work of Jean Rhys and argues that her fiction presents a pervasive and unsettling challenge to the post-Romantic notion of 'original' literary production as organically 'rooted' in 'national' culture. I first focus on Rhys's treatment of questions of authorship and appropriation in 'Again the Antilles' and 'Let Them Call It Jazz' in the light of archival documents which indicate a pervasive anxiety of originality. I then move on to examine the relationship between authorship and translation that is revealed in an early typescript draft of Rhys's only explicitly 'derivative' text, 'The Chevalier of the Place Blanche'. If 'Let Them Call It Jazz' can be seen to present the power of a nomadic, anonymous art that resists and destabilises the system of cultural capital and authorial 'ownership', a story like 'Chevalier', I argue, begins to gesture towards such an art.